Supplier selection and contract enforcement: Evidence from performance bonding - Leonardo M. Giuffrida; Gabriele Rovigatti (Journal of Economics & Management Strategy, 2022)
We analyze an important but little-studied institution for balancing supply risk in the management of procurement operations: performance bonding. By adding the surety as a third party that guarantees contract fulfillment between supplier and buyer, performance bonding aims to streamline the purchasing process by influencing both contractor selection in the bidding phase and contract enforcement during project execution. Using the data on US government procurement from 2005 to 2015 and exploiting an exogenous variation in the threshold for its application to construction contracts, we find that performance bonding improves contract outcomes by 10.5% and 3.7% in terms of delays and extra costs, respectively. Net of bond premia, which by law are included in the award amounts, this effect translates into savings of about 4% in the budget for federal construction projects and 16% for mid-size projects. We provide suggestive evidence on the effectiveness of selection and monitoring by sureties as driving channels.
Keywords: 330